Andean anthropology, "Andeanism" and the luminous path - Starn, Orin (1992)
On May 17, 1980, Shining Path militants burned the amphorae in the Andean community of Chuschi and proclaimed their intention to overthrow the Peruvian state. What Senderistas would later call the "ILA"—the beginning of the armed struggle—coincided with the 199th anniversary of the execution of Túpac Amaru II by the Spanish colonizers. According to versions of the Inkarrí myth, the corpse of the neo-Inca rebel would be destined to recompose itself in a resurrection of Andean society after the cataclysm of the conquest. But Chuschi heralded not a rebirth, but a decade of death. It inaugurated a savage war between the insurgents and the government that would cost more than 20,000 lives during the 1980s.